Assessment of the global circulation and endemicity of dengue. Issue 4 (10th July 2021) - Long, Haoyu; Zhang, Chi; Chen, Cai; Tang, Jing; Zhang, Bing; Wang, Yinghan; Pang, Jiali; Su, Wenzhe; Li, Kuibiao; Di, Biao; Chen, Yao‐Qing; Shu, Yuelong; et al.
Abstract: Dengue is a significant public health issue, affecting hundreds of millions of people worldwide. As it is spreading from tropical and subtropical zones, some regions previously recognised as non‐endemic are at risk of becoming endemic. However, the global circulation of dengue is not fully understood and quantitative measurements of endemicity levels are lacking, posing an obstacle in the precise control of dengue spread. In this study, a sequence‐based pipeline was designed based on random sampling to study the transmission of dengue. The limited intercontinental transmission was identified, while regional circulation of dengue was quantified in terms of importation, local circulation and exportation. Additionally, hypo‐ and hyper‐endemic regions were identified using a new metric, with the former characterised by low local circulation and increased importation, whereas the latter by high local circulation and reduced importation. In this study, the global circulation pattern of dengue was examined and a sequence‐based endemicity measurement was proposed, which will be helpful for future surveillance and targeted control of dengue.